Investigating the Impact of ERAS Protocols on Postoperative Outcome in Patients Undergoing Colorectal Surgery. - Bashir, Maria; Ali, Hifza Nazir; Mehmood, Yasir; Fattani, Bilal; Shafiq, Pakeeza; Siddique, Hira (Indus Journal of Bioscience Research, 2024)
Background: Enhanced Recovery After Surgery (ERAS) protocols have been increasingly adopted in colorectal surgery to improve postoperative outcomes. Objective: This study investigates the impact of ERAS protocols on postoperative outcomes in patients undergoing colorectal surgery Methods: This is a cross-sectional study conducted on 60 consecutive patients undergoing colorectal surgery at Jinnah hospital from January 2024 to August 2024. The participants were divided into two groups with 30 participants each. Group I was treated as per ERAS protocol while Group II was given traditional care. Demographic data, mean operative time, Length of hospital stay, post operative pain and post operative complication was noted in both groups. Data was assessed on SPSS version 24. Results: The mean operative time was notably shorter in Group I at 55.4 minutes compared to 64.7 minutes in Group II, (p-value=0.006). Post- operative pain, assessed via the Visual Analogue Scale, showed lower scores in Group I on all measured days: Day 1 (3.71 ± 0.97 vs. 4.69 ± 0.93, p = 0.033), Day 2 (2.32 ± 0.85 vs. 3.13 ± 0.95, p = 0.03), and Day 3 (1.49 ± 0.79 vs. 1.98 ± 0.98, p = 0.04) (Table 2). Additionally, Group I experienced a quicker return to oral intake (1.3 ± 0.4 days vs. 1.9 ± 0.7 days, p = 0.005) and mobilization (2.1 ± 0.9 days vs. 3.6 ± 1.1 days, p = 0.04). Conclusion: This study highlights the significant advantages of implementing ERAS protocols in colorectal surgery, demonstrating improved postoperative outcomes, compared to traditional care.